Perlindungan Hukum Terhadap Pekerja Di Indonesia Berdasarkan Undang-Undang Cipta Kerja - M. Bagus Basofi; Irma Fatmawati (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
Law Number 11 of 2020 concerning Job Creation in its preparation uses the Omnibus Law method which covers ten policy areas, namely: improving the investment ecosystem and business activities; employment; convenience, protection and empowerment of cooperatives and SMEs; ease of doing business; research and innovation support; land acquisition; economic area; central government investment and acceleration of national strategic projects; implementation of government administration; and imposition of sanctions. Since the beginning of the Omnibus Law "Cipta Kerja" has attracted public attention, especially in the employment cluster because it is considered to bring harm to workers. As a result, trade/labor unions rejected the existence of this Job Creation Law and held large-scale demonstrations in a number of areas.